Influence of Steel Structure on Machinability by Abrasive Water Jet - Hlaváčová, Irena M; Sadílek, Marek; Váňová, Petra; Szumilo, Štefan; Tyč, Martin (Materials (Basel, Switzerland), 2020)
Although the abrasive waterjet (AWJ) has been widely used for steel cutting for decades and there are hundreds of research papers or even books dealing with this technology, relatively little is known about the relation between the steel microstructure and the AWJ cutting efficiency. The steel microstructure can be significantly affected by heat treatment. Three different steel grades, carbon steel C45, micro-alloyed steel 37MnSi5 and low-alloy steel 30CrV9, were subjected to four different types of heat treatment: normalization annealing, soft annealing, quenching and quenching followed by tempering. Then, they were cut by an abrasive water jet, while identical cutting parameters were applied. The relations between the mechanical characteristics of heat-treated steels and the surface roughness parameters Ra, Rz and RSm were studied. A comparison of changes in the surface roughness parameters and Young modulus variation led to the conclusion that the modulus was not significantly responsible for the surface roughness. The changes of RSm did not prove any correlation to either the mechanical characteristics or the visible microstructure dimensions. The homogeneity of the steel microstructure appeared to be the most important factor for the cutting quality; the higher the difference in the hardness of the structural components in the inhomogeneous microstructure was, the higher were the roughness values. A more complex measurement and critical evaluation of the declination angle measurement compared to the surface roughness measurement are planned in future research.
Keywords: surface roughness; tensile strength; heat treatment; hardness; abrasive water jet cutting